Comparison of various surgical approaches for extensive bilateral colorectal liver metastases - Reißfelder, Christoph; Rahbari, Nuh N.; Bejarano, L. Urrutia; Schmidt, Thomas; Kortes, Nikolas; Kauczor, Hans-Ulrich; Büchler, Markus W.; Weitz, Jürgen; Koch, Moritz (Langenbeck's archives of surgery, 2014)
Tailored operative strategies have been proposed for patients with bilobar colorectal liver metastases (CLM). The aim of the study was to evaluate the long-term outcome, safety and efficacy, including cancer-specific survival, morbidity, and mortality, of three different surgical strategies for extensive bilateral CLM.
Gesehen am 19.08.2020